Effect of nitrogen sources on the yield and quality attributes of capsular polysaccharides in Streptococcus pneumoniae - Li, Yuelong; Liu, Yanli; Yao, Hantian; Wang, Yanyan; Zhou, Yechi; Zheng, Hao; Liu, Yanbin; You, Xinyan; Cao, Xin; Liu, Jiankai (Frontiers in Chemical Engineering, 2025)
Streptococcus pneumoniae, a pathogenic bacterium, is responsible for a range of infections. With the rise in antibiotic resistance, vaccination against pneumococcal disease has become increasingly critical. Pneumococcal capsular polysaccharides (CPSs) serve as potent vaccine antigens, triggering the host’s production of protective antibodies. The immunogenicity of CPS antigens in pneumococcal vaccines is significantly influenced by the chain length, the content of functional chemical groups and additional chemical modifications. S. pneumoniae has stringent nutritional requirements for culture medium. One crucial aspect of fermentation medium development is the selection of nitrogen sources. These sources supply the essential nutrients for the synthesis of vital biomolecules and secondary metabolites, including the CPSs. Therefore, comprehending the impact of organic nitrogen sources on the yield and quality of CPSs is crucial for optimizing manufacturing processes for pneumococcal vaccines. In our study, we evaluated the effects of peptones from various sources on the growth profiles and CPS yields, as well as quality attributes related to CPS immunogenicity. We found that while CPS productivity was slightly impacted by peptone selection, the chain length and functional group content of CPSs were markedly influenced by the peptone source. Notably, using the non-animal HY-SOY 4D soy peptone as a nitrogen source in the fermentation medium led to CPSs with long chains and a high content of functional chemical groups. The structural identity and correctness of pure CPSs were verified by 1H nuclear magnetic resonance (NMR) spectroscopy. The findings offer insights into how the composition of the fermentation medium affects both the yield and quality of pneumococcal CPSs, aiming at improving vaccine production against pneumococcal infections.